EFFECT OF STUDENT OPERATIONAL ASSISTANCE FUNDS (BOS) PERFORMANCE ON TEACHER TRAINING PROGRAMS AND ENCOURAGING LEARNING IN ELEMENTARY SCHOOLS - Endah Martdiyatun Wijaya; Gunawan Gunawan (SOSIOEDUKASI, 2026)
The Performance Student Operational Assistance Fund (BOS) is a form of government support in improving the quality of education, especially through strengthening teacher competence and learning quality. The purpose of this study is to determine the relationship between teacher training programs and encouraging learning. The type of research used is quantitative with a survey method. The research population is 14 schools that received BOS Performance in Cilongok District, with a sample of 3 schools, namely SDN 1 Pernasidi, SDN 2 Rancamaya, and SDN 2 Sokawera. The number of respondents was 29 people consisting of principals and teachers. The data collection technique used questionnaires, while data analysis used SPSS version 25 which included normality tests, homogeneity tests, and Pearson correlation tests. The results showed that the data were distributed normally and homogeneously, with the significance values of the normality test of 0.120 and 0.250 (> 0.05), respectively, and the homogeneity test of 0.416 (> 0.05). The results of the Pearson correlation test showed a significance value of 0.000 (< 0.05) with a correlation coefficient of 0.804 which was included in the strong category. This shows that teacher training programs have a positive and significant relationship with encouraging learning. Thus, the better the implementation of teacher training, the more the quality of interactive, interesting, and fun learning will also improve. The results of this study provide a scientific contribution in supporting the optimization of the use of the Performance BOS Fund as an effort to improve teacher competence and learning quality in elementary schools.